Young Adults’ Knowledge about Savings - Lachance, Marie J; Cloutier , Jacinthe (Nurture, 2009)
A sample of 966 young adults from the province of Quebec (Canada) participated in this study, which aimed to identify the determinants of knowledge about savings and investments and their relative importance. Our findings show that knowledge about savings and investments is rather low. Canadian-born males with high personal annual gross income and education are likely to have a higher level of knowledge in this area than their counterparts. Personal finance education, received outside of high school, attitude towards savings and having met with a personal finance professional, have a significant positive impact on this knowledge. The usefulness of financial education and the need to increase financial independence among young female adults are discussed.